2018
DOI: 10.2147/ott.s159057
|View full text |Cite
|
Sign up to set email alerts
|

Combined small-cell lung carcinoma

Abstract: Currently, studies assessing combined small-cell lung carcinoma (C-SCLC) are relatively scarce and limited. Indeed the clinicopathological features, treatment, and prognosis of patients with C-SCLC have not been fully determined. The incidence of C-SCLC ranges from 5%–28% in different studies, which is related to the specimen types used. The clinical features of C-SCLC are characterized by the higher proportion of peripheral locations, earlier stage, and more opportunity to experience surgery. Surgery is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 35 publications
(48 reference statements)
1
54
0
Order By: Relevance
“…C-SCLC is a rare tumor with independent biological characteristics (Babakoohi et al 2013 ; Qin and Lu 2018 ). Previous reports showed that up to 28% of SCLC patients who underwent surgical resection were c-SCLC (Nicholson et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-SCLC is a rare tumor with independent biological characteristics (Babakoohi et al 2013 ; Qin and Lu 2018 ). Previous reports showed that up to 28% of SCLC patients who underwent surgical resection were c-SCLC (Nicholson et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT is the main imaging tool for initial staging and influences patient management and early assessment of tumor response (Kim et al 2018 ; Zer et al 2016 ). With the development of 18 F-FDG PET/CT technology, lung cancers are diagnosed earlier and more SCLC patients undergo surgery and have pathological examinations, which have led to more c-SCLC diagnoses recently (Qin and Lu 2018 ; Zhang et al 2017 ). However, influence of primary tumor metabolic parameters and mixed NSCLC components on survival of c-SCLC, and whether they are associated with prognosis are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some cases respond to TKIs, suggesting that this treatment may be an option for patients with mutant c-SCLC. 2 Compared to SCLC, systemic chemotherapy appears to have a lower efficacy on c-SCLC; moreover, c-SCLC has a poorer prognosis, 2,22,23 but there are conflicting reports, mainly regarding limited-stage diseases. 24,25 c-SCLCs are typically treated according to SCLC regimens for extensive-stage cancer, such as platinum plus etoposide.…”
Section: Discussionmentioning
confidence: 99%
“…1 Standard chemotherapy for patients with c-SCLC remains to be established; nevertheless, c-SCLC generally appears to be less sensitive to chemotherapy compared to SCLC. 2 Only a handful of reports indicate that gene mutations, such as that of the epidermal growth factor receptor (EGFR), may be detected in patients with c-SCLC, mainly in those having the adenocarcinoma component. Moreover, little is known about the anaplastic lymphoma kinase (ALK) rearrangement in patients with c-SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is the most crucial lung cancer risk factor (3). In general, this malignancy can be categorized into Small Cell Lung Carcinoma (SCLC), Adenocarcinoma (ADC), Squamous Cell Carcinoma (SCC), and Large Cell Carcinoma (LCLC) (4). Lung carcinomas are a group of cancers arising from any part of the bronchial tree or pulmonary parenchyma.…”
Section: Introductionmentioning
confidence: 99%